‘They Might Not Kill You Today but They’re Going to Get You in the End’: the Correctional Subculture and the Schematization of Danger - Higgins, Ethan M. (The British journal of criminology, 2023)
Criminology has long investigated criminal justice cultures and their preoccupation with dangerousness. Over a half century ago, correctional scholars called for a richer understanding of how a ‘social reality’ of danger might shape the mental state of staff. More recently, correctional scholarship has demonstrated that correctional culture and perceptions of danger likely play a fundamental role in findings that staff experience conflict across domains. Drawing from 18 focus groups of correctional staff from all adult carceral facilities in one state, this study investigates: 1) how cultural workgroup concerns over danger and values of safety shape staff’s worldview broadly; and, 2) how these worldviews concerning danger shape cultural cognition outside the carceral context. To answer these questions, we draw upon cultural sociology and leverage the mechanism of the schema to understand how values are recalled across domains. Through this analysis, we illustrate how an accumulation of stories concerning danger within prison shapes a worldview that structures compulsive cognition around personal safety. We show how compulsive cognition manifests as an intrinsic knowledge of the dangerous character of others and a personal drive to fortify against underspecified violent threats outside the carceral context.